2017
DOI: 10.1149/2.0171712jss
|View full text |Cite
|
Sign up to set email alerts
|

AFM and SEM Study on Crystallographic and Topographical Evolutions of Wet-Etched Patterned Sapphire Substrate (PSS): Part III. Cone-Shaped PSS Etched in H2SO4and H3PO4Mixture at Various Temperatures

Abstract: The effect of etching temperature (473-543 K) on the crystallographic and topographical evolutions as well as the etching rate of crystallographic planes of cone-shaped patterned sapphire substrate (PSS) etched in both H 2 SO 4 -based (H 2 SO 4 :H 3 PO 4 = 5:1 at volume ratio) and H 3 PO 4 etchants was systematically studied. For H 2 SO 4 -based etchant, higher temperature favors larger etching rate ratio of slant planes (S 1 {11 0 5}, S 3 {45 1 38}, S 4 {11 0 12}, and S 5 {1 1 0 37} planes) to c-plane, thus l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
(80 reference statements)
0
20
0
Order By: Relevance
“…The etching process is controlled by the kinetics of the reaction, resulting in significant temperature dependence of the etch rates [31][32][33]. In the particular case of sapphire etched with mixtures of H 2 SO 4 and H 3 PO 4 , Shen et al have reported high activation energies (87.0-108.3 kJ mol −1 ), supporting the reactionlimited characteristics of the etching [28]. Thus, the impact of reactant diffusion can be neglected and the etching reaction can be characterized with the orientation dependence of the etch rate [7], i.e.…”
Section: Modeling Anisotropic Wet Etchingmentioning
confidence: 94%
See 2 more Smart Citations
“…The etching process is controlled by the kinetics of the reaction, resulting in significant temperature dependence of the etch rates [31][32][33]. In the particular case of sapphire etched with mixtures of H 2 SO 4 and H 3 PO 4 , Shen et al have reported high activation energies (87.0-108.3 kJ mol −1 ), supporting the reactionlimited characteristics of the etching [28]. Thus, the impact of reactant diffusion can be neglected and the etching reaction can be characterized with the orientation dependence of the etch rate [7], i.e.…”
Section: Modeling Anisotropic Wet Etchingmentioning
confidence: 94%
“…Whereas the wet etching of Si is well studied, the etch rate anisotropy of single-crystal sapphire is still being investigated. Several studies measured the etch profile evolution and characterized the crystal facets observed in the experiment [11,14,[25][26][27][28]. In these studies, only a small number of etch rate/crystal direction pairs have been identified, due to the limited number of distinct crystal facets emerging during the etching process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, two kinds of PSS samples were used to investigate the effect of modification of micron-sized PSS patterns on the GaN growth mechanism: (1) RPSS (regular PSS without etching) and (2) PSSE (RPSS etched in sulfuric–phosphoric acid (ratio 3:1) at 270 °C for 30 s). As shown in Figure 1b, 3T {11¯05} facets were observed on the pattern of PSSE [19,20,21,22,23].…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] According to the analysis of previous wet etching experiments of sapphire, a mixed solution of concentrated sulfuric acid and concentrated phosphoric acid is usually as the etchant, [12][13][14] and the etching temperature is usually in the range of 200 °C-300 °C. [15][16][17][18] Considering the operability and safety of wet etching experiments of sapphire, the etching temperature was set to 250 °C at first. However, it was found that the temperature of the solution was balanced at 236 °C.…”
mentioning
confidence: 99%